Continuous-flow/stopped-flow system using an immunobiosensor for quantification of human serum IgG antibodies to Helicobacter pylori - Messina, Germán Alejandro (2005)
Conventional methods, such as gastric biopsy, enzyme-linked immunosorbent assay (ELISA), culture, require a long time for the determination of Helicobacter pylori infections. This study reports an amperometric immunoreactor for rapid and sensitive quantification of human serum immunoglobulin G (IgG) antibodies to H. pylori. Antibodies in the serum sample are allowed to react immunologically with the purified H. pylori antigens that are immobilized on a rotating disk. The bound antibodies are quantified by horseradish peroxidase (HRP) enzyme-labeled second antibodies specific to human IgG. HRP in the presence of hydrogen peroxide catalyzes the oxidation of hydroquinone to p-benzoquinone. The electrochemical reduction back to hydroquinone is detected on a glassy carbon electrode surface at -0.15 V. The electrochemical detection can be done within 1 min, and the analysis time does not exceed 30 min. The calculated detection limits for amperometric detection and the ELISA procedure are 0.6 and 1.9 U ml-1, respectively. The amperometric immunoreactors showed higher sensitivity and lower time consumed than did the standard spectrophotometric detection ELISA method. It can also be used for rapid analysis in conventional and field conditions in biological, physiological, and analytical practices.